Retextualização : uma estratégia para desenvolver competências escritas em alunos do 9º ano do ensino fundamental - Silva, Gleice Rayane Macedo (2018)
The social transformations that the world has faced, due to distance reduction between rural and urban areas or the increase in the use of technologies, have linked several individuals’ social activities to writing practice. Teaching strategies adopted at schools had to be rethought as a consequence of such social dynamic, a change that was reinforced by the progress of scientific studies within the educational field. As a result, teachers have to seek new ways for promoting their students’ social inclusion by adopting different teaching strategies at schools. This paper arises from this movement towards the improvement of student’s performance when using Portuguese Language. Thus, this report presents the results of a pedagogical intervention in the 9th grade class of elementary education of Alfredo Montes State School (CEAM), in Nossa Senhora do Socorro city – state of Sergipe – that showed demands for better written production. This research was developed in the ambit of the Professional Master’s Degree in Portuguese Language – PROFLETRAS, São Cristóvão campus, of Federal University of Sergipe, and it was conducted according to action research methodology by Tripp (2005), having as its focus the students’ written contextual adequacy. We started from the hypothesis that retextualization could help decrease the classroom’s demands. The intervention aim was the students’ written competences development, by adopting retextualization as a strategy for comparative teaching of written genre, offering an opportunity to create news from a short story. For this, we prepared a Pedagogical Activities Notebook for students that contains teacher’s guidance, which was incorporated into a Didactic Sequence created by performing an intersection between the sequences of Cosson (2016) and Dolz, Noverraz and Schneuwly (2004), aiming to attenuate the identified difficulty within the mentioned class. The Notebook and the Didactic Sequence were produced based upon the theoretical and methodological approaches of Bronckart (2006), concerning the Socio-discursive Interactionism, whose text concept was adopted, regulating the treatment granted to other studies, for instance retextualization by Dell’Isola (2007) and Marcuschi (2010); contextualization by Koch and Elias (2015b), Baltar (2003) and Lima (2010); reading strategies by Solé (1998) and Koch and Elias (2015a), also suggestions about text production by Passarelli (2012). In addition to that, the interactive correction by Soares (2009) and official documents suggestions that guide teacher’s professional practice, such as National Common Curricular Base (BNCC) and the Portuguese National Curricular Parameters (PCNLP). The results revealed that the production of texts in a direct language is a complex task for those students who are not accustomed to write objectively, and that this practice has to be provided regularly at schools, in order to offer students the opportunity to learn other languages effectively. Finally, the research participants’ text productions showed different levels of contextual and genre adequacies, according to the adopted text evaluation criteria, indicating that the systematized teaching of retextualization is a viable way for leading them to write in a contextualized manner.